The Influence of the Physical Environment of Class III Inpatient Rooms on Patient Satisfaction at Tgk Abdullah Syafi'i Beureunuen Hospital - Rakhman, Fakhryan; Nurrahmah, Riska; Kartika; Ismuntania; Mualim, Azhar (International Journal on ObGyn and Health Sciences, 2024)
Hospitals must meet the technical requirements of hospital facilities and infrastructure that support complete health services. The facts show that the increase in patient satisfaction is influenced by the quality of the physical facilities of the ward. This study aimed to influence the comfort of the physical environment of Class III Inpatient Room on patient satisfaction at Tgk Chik Di Tiro Regional General Hospital Sigli in 2022. This is an analytical study with a survey approach. The location was at Tgk Chik Di Tiro Hospital Sigli. The population was 134 people and the sample was 93 people. The sampling technique used proportional random sampling. The independent variables include air quality, temperature, humidity, room layout, noise, floor conditions, ceiling and lighting conditions, while the dependent variable is patient satisfaction. Data analysis used chi-square and multiple logistic regressions. The results showed that the variables of air quality (p = .009), temperature (p = .002), room layout (p = .013), noise (p = .018) and floor conditions (p = .006) had a significant effect on inpatient satisfaction at the Hospital. It can be concluded that temperature is the dominant variable influencing the satisfaction of inpatients at Tgk Chik Ditiro Sigli Hospital. It is suggested to the hospital manager to improve the hospital physical quality such as temperature, air quality, noise or other physical environment in order to improve the hospital's image and customer satisfaction